2022
DOI: 10.1186/s40792-022-01358-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary treatment of advanced or recurrent solid pseudopapillary neoplasm of the pancreas: three case reports

Abstract: Background Solid pseudopapillary neoplasm (SPN) is a rare pancreatic tumor that predominantly affects young females. Prognosis is excellent; however, 10–15% of patients show metastasis at the time of surgery or develop tumor recurrence after pancreatectomy. Case presentation We reviewed the clinical course of three patients with advanced or recurrent SPN and subsequently underwent multidisciplinary treatment at our institution between 2002 and 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…In the presented case reports no treatments were offered to the patients. Wojciak et al described a case of lymph node recurrence 1 year after transplantation that was treated with excision, radiotherapy, and switching to mTOR inhibition immunosuppression [4]. Lymph node status was carefully evaluated in our case.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the presented case reports no treatments were offered to the patients. Wojciak et al described a case of lymph node recurrence 1 year after transplantation that was treated with excision, radiotherapy, and switching to mTOR inhibition immunosuppression [4]. Lymph node status was carefully evaluated in our case.…”
Section: Discussionmentioning
confidence: 91%
“…However, 10-15% of cases of SPN have metastatic disease at the time of diagnosis and the most common site is the liver. Tanue et al reported that in patients with malignant feature SPN, liver metastasis occurs in 57.1% of cases [4]. Sperti et al reported occurrence of hepatic metastasis 2-168 months after diagnosis of the primary tumor [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation therapy has been successfully used for recurrent tumors with good long-term prognosis. (28,29)…”
Section: Resultsmentioning
confidence: 99%
“…The prognosis is favorable even in the presence of distant metastases. Recurrence rates are low, and 5 year survival as high as 97% [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%